THE CONCEPT OF “MENTALITY” IN THE CONTEXT OF TRANSLATION THEORY AND INTERCULTURAL COMMUNICATION. - Kosimov Ulugbek Abdullaevich (International Journal of Literature and Language Studies, 2026)
The article examines the concept of mentality as an important category in modern translation studies reflecting national patterns of perception and value systems. The study analyzes major theoretical approaches to the interpretation of mentality in the humanities and substantiates the necessity of considering mental and cultural factors in the process of transferring meaning between languages. Particular attention is paid to the problem of conveying culturally determined meanings in intercultural communication. Based on Uzbek-Russian linguistic material and literary texts, the research demonstrates that neglecting national worldviews may lead to semantic and pragmatic distortions.